Risiko Ketidakpatuhan Syariah dan Pelaporan Pengungkapannya pada Perbankan Syariah di Indonesia - Pranoto Effendi; Addys Aldizar (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
Islamic banking in Indonesia is growing rapidly, with average asset growth of around 14% per year since 2019. However, its contribution to the national financial system remains relatively small, with an asset share of only 3.78% and a market share of 10.95%. One factor limiting this growth is public perception regarding Islamic banks’ compliance with Sharia principles. Sharia compliance risks are a major concern as they impact the credibility, sustainability, and legitimacy of Islamic banks in the eyes of the public. This article analyzes the practices of Sharia compliance risk management and disclosure in Indonesian Islamic banking based on a qualitative study of Islamic banks’ annual reports. The analysis includes an evaluation of the role of the compliance function, the Sharia Supervisory Board (SSB), control mechanisms, and reporting of non-halal income and its allocation. Primary data were obtained through content analysis of the 2023 annual reports of Bank Muamalat Indonesia and Bank Mega Syariah, which were then reviewed using descriptive-analytical techniques. The findings indicate that the SSB and the compliance function are the primary actors in risk management, with minimal implementation in accordance with regulations (monthly meetings, spot checks, coordination with management and the Financial Services Authority). However, disclosure is normative and limited: details of non-compliance, root causes, incident number, and details of non-halal income are often not disclosed. Empirical findings also reveal differences in the management practices and treatment of non-halal income. This study recommends increased transparency: disclosing the number of non-compliance incidents, types of violations, the value of non-halal income, causes, corrective actions, and the distribution mechanism for charitable funds. More comprehensive disclosure will increase public trust, strengthen governance, and support the development of Islamic banking. Suggestions for further research include conducting comparative studies between banks and analyzing the impact of transparency on customer trust and investor interest.